2017
DOI: 10.1177/0951484817696213
|View full text |Cite
|
Sign up to set email alerts
|

Journal rankings and directions for future research in health care management: A global perspective

Abstract: Despite the increasingly global nature of health care, much of the research about journal rankings and directions for future research in health care management is from a United States based viewpoint. There is a lack of information about influential journals and trends for health care management research from a global perspective. This exploratory study gathered the opinions of health care management researchers from 17 countries regarding which journals are considered most influential, popular research topics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The protocol also recommends utilizing the opinions of faculty and librarians in the field. Recent surveys of health care research and management faculty members and researchers have affirmed the importance of these five journals [9][10][11]. The participants in Borkowski et al's study ranked these journals as the top five most relevant health-related titles as potential publishing sources for HCM research [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol also recommends utilizing the opinions of faculty and librarians in the field. Recent surveys of health care research and management faculty members and researchers have affirmed the importance of these five journals [9][10][11]. The participants in Borkowski et al's study ranked these journals as the top five most relevant health-related titles as potential publishing sources for HCM research [11].…”
Section: Methodsmentioning
confidence: 99%
“…The participants in Borkowski et al's study ranked these journals as the top five most relevant health-related titles as potential publishing sources for HCM research [11]. Meese et al found that all five titles were among the top twenty most influential journals in HCM according to the opinion of international experts, with HCMR (rank=1), HA (rank=2), HSR (rank=4), and JHM (rank=6) in the top ten [10]. Menachemi and DelliFraine surveyed health administration faculty members and found that all five of this study's source journals were ranked in the top ten health administration journals, with HA, HSR, HCMR, and JHM in the top five [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we want to address such challenges effectively, we need research that does justice to their inherently universal nature. In other words, we need more rigorous cross-country comparative research.In many of the "top" health care management journals (according to Meese et al, 2017), upward of 96% of all contributions in the past few years stem from one country, according to our own analysis of Clarivate data. At HCMR, almost two thirds of the contributions are from one country.…”
mentioning
confidence: 92%
“…In the literature, several studies propose new or updated ranking methods either at specific discipline- or field levels, or across all academic journals (Bornmann et al , 2016; Carraher and Paridon, 2015; Gursoy and Sandstrom, 2016; Horrace and Parmeter, 2017; Mahmood, 2017; Meese et al , 2017; Okumus et al , 2017; Tourish and Willmott, 2015; Tüselmann et al , 2015). These studies have primarily relied on either the basic or advanced formulations, including the citation count of journals or the stated preferences or expertise obtained via surveys.…”
Section: Introductionmentioning
confidence: 99%